Large-volume hyperthermia for safe and cost-effective targeted drug delivery using a clinical ultrasound-guided focused ultrasound device - Lyon, PC; Mannaris, C; Gray, M; Carlisle, R; Gleeson, FV; Cranston, D; Wu, F; Coussios, CC (Elsevier, 2021)
Lyso-thermosensitive liposomes (LTSLs) are specifically designed to release chemotherapy agents under conditions of mild hyperthermia. Preclinical studies have indicated that magnetic resonance (MR)-guided focused ultrasound (FUS) systems can generate well-controlled volumetric hyperthermia using real-time thermometry. However, high-throughput clinical translation of these approaches for drug delivery is challenging, not least because of the significant cost overhead of MR guidance and the much larger volumes that need to be heated clinically. Using an ultrasound-guided extracorporeal clinical FUS device (Chongqing HAIFU, JC200) with thermistors in a non-perfused ex vivo bovine liver tissue model with ribs, we present an optimised strategy for rapidly inducing (5–15 min) and sustaining (>30 min) mild hyperthermia (ΔT <+4°C) in large tissue volumes (≤92 cm3). We describe successful clinical translation in a first-in-human clinical trial of targeted drug delivery of LTSLs (TARDOX: a phase I study to investigate drug release from thermosensitive liposomes in liver tumours), in which targeted tumour hyperthermia resulted in localised chemo-ablation. The heating strategy is potentially applicable to other indications and ultrasound-guided FUS devices.